Stability analysis of a laser model for buried heterostructure stripe lasers - Poh, B. S.; Poh, L. K.; Yap, C. L. (Malaysian Institute of Physics, 1984)
A laser model consisting of a set of rate equations for the photon density and carrier density is analysed to determine its temporal stability. It is found that the model is always stable when a linear gain expression is used. No self-sustained oscillation in the light output is observed. A comparison is made with the results obtained from a similar model which incorporates a logarithmic gain instead of a linear gain. It is found that the stability in the linear gain model does not necessarily indicate that buried heterostructure lasers are inherently stable. Rather, it indicates that the type of gain expression used in the laser model is an important consideration in the study of the dynamics of the laser.